A APLIKASI PENGOLAHAN NILAI RAPOR KELAS DI SEKOLAH DASAR MASEHI LAIMBONGA BERBASIS WEB: Application, Value Processing, Report Card, Waterfall, Website - Melqan Radjah, Rizaldy Adiwanto (STMIK Hang Tuah Pekanbaru, 2022)
SD Masehi Laimbonga in processing the final score of the report card takes a long time in the value processing process so that there is a delay in reporting because many assessment criteria are determined. The purpose of this research is to assist teachers in accelerating the value processing process so as to produce digital student report cards. The research method used is the waterfall model starting from the analysis, design, implementation and testing stages. This research produces an application that helps teachers in accelerating the processing of grade report cards. The application generates report cards which can be directly downloaded as PDF files. The test produces output that is in accordance with the input from the teacher and proves the difference in time for processing report cards for 1 student manually takes 8 minutes 43 seconds while the application is 2 minutes 14 seconds.